Ulcerative skin lesions – what is the diagnosis? - Foles, Ana; Carvalho, Rita; Moreira, Biana; Cachão, Joana (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
Ecthyma is an ulcerative skin infection, usually caused by group A beta-hemolytic Streptococcus. High temperatures and humidity facilitate the development of the disease, which is particularly common among travelers returning from tropical countries. Early diagnosis and adequate treatment, with systemic antibiotics and local intervention, is essential to minimize the risk of complications. The authors present the case of an 11-year-old boy with exuberant ecthyma lesions conditioning severe pain, which prevented walking.